TRAINING AND ASSISTANCE IN PREPARING HOTS QUESTIONS BASED ON DIGITAL LITERACY PEDAGODIC-CHEM FOR CHEMISTRY TEACHERS IN DONGGALA REGENCY - Rahmawati, Sitti; Pathuddin, Pathuddin; Ahmar, Dewi Satria (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Higher order thinking skills or abbreviated as HOTS is an ability that is applied in the revised 2013 Curriculum. Teachers are required to be able to create Higher Order Thinking Skills (HOTS) oriented questions, namely questions whose questions are able to train students to think at a high level of analysis, evaluation, and creation. The provision of HOTS questions aims to create challenging learning for students to reflect and apply their reasoning. However, the reality in the field based on interviews and the distribution of needs analysis questionnaires among chemistry teachers obtained data of 50% in the classification of good enough for indicators of knowledge of HOTS questions, indicating that the level of preparation of HOTS questions for chemistry teachers is not optimal. Most of the questions given are still at the LOTS level, because it is difficult to find the accuracy of the level of questions that are reached by students' abilities. Partners have not used pedagogic-chem strategies to develop HOTS questions, such as the use of contexts that are relevant to students' lives. Teachers who are members of the Chemistry Subject Teacher Conference (MGMP) as partners of this service still experience problems in analyzing the forms of questions that can improve higher order thinking skills (HOTS). To overcome this problem, training and mentoring with a participatory model were conducted, which included: a) introducing the concept, function, and purpose of HOTS questions to face 21st century skills, b) introducing the utilization of HOTS questions in learning evaluation along with applicable and principle steps, c) guiding teachers to create a bank of HOTS questions according to the division of domains and aspects of measuring HOTS achievement, d) guiding teachers in direct practice in mapping HOTS questions to the achievement of learning objectives in the process of achieving pedagogic-Chem, e) mentoring online and offline in the process of developing HOTS question banks obtained digitally and conventionally systematically, f) mentoring in utilizing digital information through relevant sources in making HOTS questions, g) mentoring in the process of searching for various information that can be managed and developed into HOTS questions based on digital literacy, and h) mentoring in the pedagogic-Chem evaluation process of HOTS question testing in the classroom productively. These activities have been carried out well thanks to good cooperation with various parties. This is illustrated by the outputs in the form of HOTS questions that the participants have made from the training and mentoring results of this service. The final result of this service is in accordance with the expected target, namely the book of HOTS questions produced which is used in chemistry learning.